Biallelic antigen escape is a mechanism of resistance to anti-CD38 antibodies in multiple myeloma - Diamond, Benjamin; Baughn, Linda; Poorebrahim, Mansour; Poos, Alexandra M; Lee, Holly; Kaddoura, Marcella; Wiedmeier-Nutor, J Erin; Durante, Michael; Otteson, Gregory; Jevremovic, Dragan; Tang, Hongwei; Fröhling, Stefan; et al. (Blood, 2025)
Monoclonal antibodies targeting CD38 are a therapeutic mainstay in multiple myeloma (MM). Although they have contributed to improved outcomes, most patients still experience disease relapse, and little is known about tumor-intrinsic mechanisms of resistance to these drugs. Antigen escape has been implicated as a mechanism of tumor-cell evasion in immunotherapy. Yet, it is unknown whether MM cells can develop permanent resistance to anti-CD38 antibodies by acquiring genomic events leading to biallelic disruption of the CD38 gene locus. Here, we analyzed whole-genome and whole-exome sequencing data from patients 701 newly diagnosed MM, 67 patients at relapse with naivety to anti-CD38 antibodies, and 50 patients collected at relapse after anti-CD38 antibodies. We report a loss of CD38 in 10 of 50 patients (20%) after CD38 therapy, 3 of whom exhibited a loss of both copies. Two of these cases showed convergent evolution in which distinct subclones independently acquired similar advantageous variants. Functional studies on missense mutations involved in biallelic CD38 events revealed that 2 variants, L153H and C275Y, decreased binding affinity and antibody-dependent cellular cytotoxicity of the commercial antibodies daratumumab and isatuximab. However, a third mutation, R140G, conferred selective resistance to daratumumab, while retaining sensitivity to isatuximab. Clinically, patients with MM are often rechallenged with CD38 antibodies after disease progression and these data suggest that next-generation sequencing may play a role in subsequent treatment selection for a subset of patients.
Keywords: alely; únik nádoru z imunitní kontroly; monoklonální protilátky; humanizované monoklonální protilátky; Humans; Membrane Glycoproteins; Alleles; ženské pohlaví; membránové glykoproteiny; antigeny CD38; Female; mužské pohlaví; Male; ADP-ribosyl Cyclase 1; Antibodies, Monoclonal, Humanized; mnohočetný myelom; Drug Resistance, Neoplasm; Antibodies, Monoclonal; lidé; chemorezistence; Tumor Escape; Multiple Myeloma